Entertainment computing - ICEC 2011 10th international conference, ICEC 2011, Vancouver, Canada, October 5-8, 2011. proceedings - Anacleto, Junia Coutinho; Fels, Sidney; Graham, Nicholas; Kapralos, Bill; Saif El-Nasr, Magy; Stanley, Kevin (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 10th International Conference on Entertainment Computing, ICEC 2011, held in Vancouver, Canada, in October 2011, under the auspices of IFIP. The 20 revised long papers, 18 short papers and 24 poster papers and demos presented were carefully reviewed and selected from 94 initial submissions. The papers cover all main domains of entertainment computing, from interactive music to games, taking a wide range of scientific domains from aesthetic to computer science. The papers are organized in topical sections on story, active games, player experience, camera and 3D, educational entertainment, game development, self and identity, social and mobile entertainment; plus the four categories: demonstrations, posters, workshosp, and tutorial.